2008
DOI: 10.1177/0269881106081529
|View full text |Cite
|
Sign up to set email alerts
|

Chlorpromazine attenuates pancreatic β-cell function and mass through IRS2 degradation, while exercise partially reverses the attenuation

Abstract: We investigated the effect and mechanism of exercise and chlorpromazine (CPZ), a conventional anti-psychotic drug, on beta-cell function and mass in 90% pancreatectomized (Px) male rats. The diabetic Px rats were divided into two groups, one of which was provided with exercise whereas the other was not. Both groups were subdivided into the three groups and administered with 0, 5 or 50 mg CPZ per kg body weight (control, low dosage of chlorpromazine (LCPZ), high dosage chlorpromazine (HCPZ)) for 8 weeks. LCPZ d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…The effect of exercise on β‐cell mass has not been examined in humans. Studies have, however, directly explored the effect of exercise training on β‐cell mass in animal models, primarily murine and rat models of diabetes (Choi et al., 2006, Choi, Jang, & Park, 2005, Coskun, Ocakci, Bayraktaroglu, & Kanter, 2004, Huang et al., 2011, Kiraly et al., 2007, Kiraly et al., 2008, Laker et al., 2011, Li et al., 2013, Park et al., 2008, Park et al., 2008, Park, Hong, Lee, & Sung, 2007, Park, Kim, & Kang, 2013, Pold et al., 2005). Diabetes was induced in these models either chemically (streptozotocin or chlorpromazine) or via surgical pancreatectomy.…”
Section: Effect Of Exercise On β‐Cell Massmentioning
confidence: 99%
See 4 more Smart Citations
“…The effect of exercise on β‐cell mass has not been examined in humans. Studies have, however, directly explored the effect of exercise training on β‐cell mass in animal models, primarily murine and rat models of diabetes (Choi et al., 2006, Choi, Jang, & Park, 2005, Coskun, Ocakci, Bayraktaroglu, & Kanter, 2004, Huang et al., 2011, Kiraly et al., 2007, Kiraly et al., 2008, Laker et al., 2011, Li et al., 2013, Park et al., 2008, Park et al., 2008, Park, Hong, Lee, & Sung, 2007, Park, Kim, & Kang, 2013, Pold et al., 2005). Diabetes was induced in these models either chemically (streptozotocin or chlorpromazine) or via surgical pancreatectomy.…”
Section: Effect Of Exercise On β‐Cell Massmentioning
confidence: 99%
“…Experimental studies have shown that there are three main mechanisms leading to increased β‐cell mass (Choi et al., 2005, Choi et al., 2006, Coskun et al., 2004, Kiraly et al., 2007, Kiraly et al., 2008, Laker et al., 2011, Park et al., 2007, Park et al., 2008, Park et al., 2008, Park et al., 2013, Paula et al., 2015, Pold et al., 2005). These can be divided into increased β‐cell proliferation, reduced β‐cell death (apoptosis), or increased β‐cell viability.…”
Section: Effect Of Exercise On β‐Cell Massmentioning
confidence: 99%
See 3 more Smart Citations